Heat Shock Protein Expression During Gametogenesis and Embryogenesis - A. Neuer; S. D. Spandorfer; P. Giraldo; J. Jeremias; S. Dieterle; I. Korneeva; H.-C. Liu; Z. Rosenwaks; S. S. Witkin (Hindawi Limited, 1999)
When cells are subjected to various stress factors, they increase the production of a group of proteins called heat shock proteins (hsp). Heat shock proteins are highly conserved proteins present in organisms ranging from bacteria to man. Heat shock proteins enable cells to survive adverse environmental conditions by preventing protein denaturation. Thus the physiological and pathological potential of hsps is enormous and has been studied widely over the past two decades. The presence or absence of hsps influences almost every aspect of reproduction. They are among the first proteins produced during mammalian embryo development. In this report, the production of hsps in gametogenesis and early embryo development is described. It has been suggested that prolonged and asymptomatic infections trigger immunity to microbial hsp epitopes that are also expressed in man. This may be relevant for human reproduction, since many couples with fertility problems have had a previous genital tract infection. Antibodies to bacterial and human hsps are present at high titers in sera of many patients undergoing in vitro fertilization. In a mouse embryo culture model, these antibodies impaired the mouse embryo development at unique developmental stages. The gross morphology of these embryos resembled cells undergoing apoptosis. The TUNEL (terminal deoxynucleotidyl transferase-mediated X-dUTP nick end labeling) staining pattern, which is a common marker of apoptosis, revealed that embryos cultured in the presence of hsp antibodies stained TUNEL-positive more often than unexposed embryos. These data extend preexisting findings showing the detrimental effect of immune sensitization to hsps on embryo development. Infect. Dis. Obstet. Gynecol. 7:10-16, 1999.